All‐Ceramic Coding Metastructure for High‐Temperature RCS Reduction. Issue 8 (18th January 2022) - Ji, Chen; Peng, Jinqiang; Yuan, Liming; Huang, Cheng; Luo, Xiangang
Abstract : Metasurfaces provide a new avenue for backscattering reduction due to their strong capability of manipulating electromagnetic wave. However, most of the previously reported low‐scattering metasurfaces are very sensitive to temperature and their performance will be disabled under high‐temperature environment. Herein, an all‐ceramic metastructure is proposed for high‐temperature backscattering reduction at microwave frequencies. Such a metastructure consists of two kinds of refractory ceramics such as Al2 O3 and TiB2 . The ceramics of Al2 O3 adopts two different coding meta‐atoms for generating 1‐bit reflection phase, while the ceramics of TiB2 acts as a metallic reflection plane due to its good electrical conductivity. Wideband radar‐cross‐section (RCS) reduction can be realized with appropriate arrangement of the coding meta‐atoms. Both the simulated and experimental results have demonstrated that the proposed all‐ceramic metastructure can achieve 10 dB RCS reduction over a wide frequency band ranging from 4.9 to 13.1 GHz, and its RCS reduction property is still remained even as the environment temperature is increased to 1000 °C. In addition, it has good angle stability under oblique incidence; good thermal stability is also verified by long‐term temperature test and thermal‐cycling test. This study provides a simple way to construct the low‐scattering material in high‐temperature applications. Abstract : An all‐ceramic metastructure is presented to achieve wideband backscattering reduction at high temperature. By designing 1‐bit reflection phase cells with the optimized distribution, the 10 dB RCS reduction can be obtained over a wide frequency band ranging from 4.9 to 13.1 GHz, and its physical property has almost no variation from ambient temperature to 1000 °C.